1993
DOI: 10.1111/j.1439-0507.1993.tb00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous sporotrichosis in the period 1978–1992 in the province of Bari, Apulia, Southern Italy

Abstract: Summary. The authors report 16 cases of cutaneous sporotrichosis observed in the province of Bari, southern Italy, since 1978. While no more than 55 cases have been documented in other European countries in the last 30 years, in Italy 58 cases (present series included) have been recorded in the same time period. Furthermore, 42 of them (73.7%) originated from Apulia. This unexpectedly high incidence rate in Italy, and in Apulia in particular, provides evidence of the important role played by this area in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…These data support the hypothesis that lesions start from local trauma after the manipulation of objects (farmers) or animal scratches or bites 8,17 . Interestingly, our study demonstrated a significant association between lymphocutaneous form and location in the upper limbs, confirming data found in the literature that suggest dissemination through the lymphatic pathway after the initial injury 11,14,18,19 . In the same way, our study demonstrated an association between the fixed cutaneous form and the lower limb location.…”
Section: Classification Of Sporotrichosissupporting
confidence: 91%
See 1 more Smart Citation
“…These data support the hypothesis that lesions start from local trauma after the manipulation of objects (farmers) or animal scratches or bites 8,17 . Interestingly, our study demonstrated a significant association between lymphocutaneous form and location in the upper limbs, confirming data found in the literature that suggest dissemination through the lymphatic pathway after the initial injury 11,14,18,19 . In the same way, our study demonstrated an association between the fixed cutaneous form and the lower limb location.…”
Section: Classification Of Sporotrichosissupporting
confidence: 91%
“…In the same way, our study demonstrated an association between the fixed cutaneous form and the lower limb location. Few published studies have shown this association, allowing only speculative hypotheses 11,18,19 .…”
Section: Classification Of Sporotrichosismentioning
confidence: 98%
“…In 457 patients, the fixed cutaneous form was more common (55.14%), which is similar to reports from China 9 . But in many different countries, lymphocutaneous form was the most commonly seen type, 21–26 although some other reports showed equal proportion of the two forms 16–17,27 . Possible causes for the different clinical forms include the size and depth of the inoculums, the genotype of the fungus, 28 and the immune status of the host 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Sporotrichosis has a higher prevalence in tropical and temperate zones and appears only sporadically in Europe [ 1 ]. In Italy, only 58 cases of cutaneous sporotrichosis have been described until 1992 [ 2 ] and a few others have been added to the literature in the last 20 years. To the best of our knowledge, only two cases of sporotrichosis in inflammatory arthritis patients treated with biologics have been described to date.…”
Section: Discussionmentioning
confidence: 99%